UPAYA MENINGKATKAN PEMAHAMAN MATERI TURUNAN FUNGSI ALJABAR DENGAN METODE DISKUSI - Lusi Rachmiazasi Masduki; Sutopo; Khotimah, Chusnul (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Terbuka, 2023)
This research was motivated by the low learning outcomes of 11 IPS 3 students at SMA Negeri 1 Pare Kediri in the mathematics subject chapter on derivatives of algebraic functions. Students' understanding of the material is seen from the cognitive domain, which only reaches less than 30% completeness. The aim of this research is to describe the increase in students' understanding of the material Deriving Algebraic Functions. The discussion method was chosen because this method is considered effective for increasing students' understanding of the difficulty. This discussion method is applied to material derived from algebraic functions using student worksheets with division into groups consisting of 4-5 people. After that, students present their results and discuss them with students in the same class. Using the discussion method resulted in an increase in understanding in the cognitive domain of 38.51%. This data was obtained from cycle 1 which produced an average test score of 47.68% with completeness reaching 18.18%. In cycle 2, improvements to the student worksheets were able to produce an average test score of 86.19% with completion reaching 81.81%. Students are also able to process emotions and appreciate expressing opinions when discussing with groups or when expressing opinions in public.